In vitro antimicrobial activity of aqueous extracts from Lentinula edodes isolates against Colletotrichum sublineolum and Xanthomonas axonopodis pv. Passiflorae - Tonucci-Zanardo,Nivea Maria (2015)
The aim of this study was to evaluate the antimicrobial activity of aqueous extracts from fruiting bodies of different isolates of Lentinula edodeson the pathogens Colletotrichum sublineolum, the causal agent of anthracnose in sorghum, and Xanthomonas axonopodispv. passiflorae, the causal agent of bacterial spot in passion fruit. Results showed that the aqueous extracts from isolates LE JAB-K and LE 95/01 significantly reduced C. sublineolumspore germination,while the isolate LE 96/22 was the only one to inhibit the pathogen mycelial growth. However, all L. edodesisolates showed inhibitory effect on C. sublineolumappressorium formation. Regarding X. axonopodispv. passiflorae, the aqueous extracts from all L. edodesisolates significantly reduced the in vitromultiplication of the bacterium. However, antimicrobial activity was lost when the extracts were autoclaved, demonstrating their thermolabile property. The aqueous extract from isolate LE 96/22 was also partially purified by anion exchange chromatography and fraction V exhibited high inhibitory activity on the in vitromycelial growth of C. sublineolum, while the multiplication of X. axonopodispv. passifloraewas inhibited by fractions IV, V and VII. Thus, L. edodesisolates were shown to produce compounds exhibiting antifungal and antibacterial activities against phytopathogens, which are mainly concentrated in fraction V.